The Effects of Computer-Based and Motor-Imagery Training on Scoring Ability in Lacrosse - Hirao, Takahiro; Masaki, Hiroaki (Frontiers in Psychology, 2020)
Previous studies have confirmed that the temporal attentional control created by the repetition of stimulus-response compatibility (SRC) tasks was transferred to shooting skills in lacrosse players. In the current study, we investigated whether combining motor imagery training with SRC tasks could enhance the scoring ability of lacrosse players. We grouped 33 male lacrosse players into three groups: an SRC task and motor imagery group (referred as to SRC+Image), an SRC task group, and a control group. Players in the first two groups underwent five sessions of 200 SRC task trials. In addition, the SRC+Image group completed five sessions of motor imagery training. The control group underwent no training interventions. All three groups performed a lacrosse shooting test and a Simon task before and after training sessions to assess the magnitude of the interference effects of the various types of training they underwent. The results of the Simon task showed that repetition of 1,000 trials was enough to create a short-term representation with the incompatible special mapping being transferred to a dynamic activity like lacrosse shooting. Moreover, combination of a computer-based Type 2 task and motor-imagery training could effectively increase players’ scoring ability in a field of large spatial conflict.